Government Financial Management : Issues and Country Studies. (International Monetary Fund, 1990)
Edited by A. Premchand, this collection of seminar papers and country studies examines recent developments in government accounting and financial management in selected industrial and developing countries. The country studies include Australia, Canada, China, India, Poland, Sweden, Turkey, the United Kingdom, the United States, and Latin American countries.